A Comparative Study of Tellurite Toxicity in Normal and Cancer Cells - Vasquez-Guzman, C (2012)
Data regarding tellurium (Te) toxicity are scarce but metabolic studies in bacteria highlight a major role of reactive oxygen species (ROS). Concentration- and time-dependent cell death has been reported in cancer cells exposed to inorganic tellurite. However, the potential in vitro effect that tellurite could generates in non-transformed human cells is still unknown. Therefore, we have studied the toxicity of inorganic tellurite (K2TeO3) in both freshly isolated peripheral blood leukocytes and in human chronic myeloid leukemia cells (K562 cells). Interestingly, we observed higher increases of ROS in leukocytes after treatment with tellurite, as compared to K562 cells. Given the high reactivity of tellurite with glutathione (GSH), a mechanism that leads to ROS formation (and mainly superoxide anion), we postulate that such a difference between cancer and normal cells is likely due to the higher GSH contents found in leukocytes versus leukemia cells. Taken together, our data point out the major differences that can be observed between cancer and corresponding normal cells in studies looking for in vitro toxicity. © 2012 The Korean Society of Toxicogenomics and Toxicoproteomics and Springer Science+Business Media Dordrecht.